2013
DOI: 10.1186/bcr3427
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis in breast cancer screening: the importance of length of observation period and lead time

Abstract: BackgroundOverdiagnosis in breast cancer screening is a controversial topic. One difficulty in estimation of overdiagnosis is the separation of overdiagnosis from lead time that is the advance in the time of diagnosis of cancers, which confers an artificial increase in incidence when a screening programme is introduced.MethodsWe postulated a female population aged 50-79 with a similar age structure and age-specific breast cancer incidence as in England and Wales before the screening programme. We then imposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 17 publications
4
80
2
1
Order By: Relevance
“…The most recent estimate on how long women should be followed after they are screened to thoroughly eliminate lead time bias is 30 years [52].Time of assessment on the RCTs averaged 12 years and ranged from 8 to 19 years (Table 4) www.TheOncologist.com ©AlphaMed Press 2014 Bleyer As to evidence of overdiagnosis of invasive breast cancer per se, we did estimate the frequency of overdiagnosis of invasive breast cancer in our original report [2] under the assumption that all cases of DCIS were overdiagnosed. This analysis suggested that invasive disease accounted for about half of all overdiagnoses and that about 20% of all invasive breast cancers were overdiagnosed, estimates that replicate those of other studies [26].To the extent that less than 100% of DCIS is overdiagnosed, the amount of invasive disease that is overdiagnosed must be proportionately greater.…”
Section: Using [Our] Methods There Is No Evidence Of Overdiagnosis Omentioning
confidence: 99%
“…The most recent estimate on how long women should be followed after they are screened to thoroughly eliminate lead time bias is 30 years [52].Time of assessment on the RCTs averaged 12 years and ranged from 8 to 19 years (Table 4) www.TheOncologist.com ©AlphaMed Press 2014 Bleyer As to evidence of overdiagnosis of invasive breast cancer per se, we did estimate the frequency of overdiagnosis of invasive breast cancer in our original report [2] under the assumption that all cases of DCIS were overdiagnosed. This analysis suggested that invasive disease accounted for about half of all overdiagnoses and that about 20% of all invasive breast cancers were overdiagnosed, estimates that replicate those of other studies [26].To the extent that less than 100% of DCIS is overdiagnosed, the amount of invasive disease that is overdiagnosed must be proportionately greater.…”
Section: Using [Our] Methods There Is No Evidence Of Overdiagnosis Omentioning
confidence: 99%
“…To the extent that some overdiagnosis of breast cancer may occur, to be reliable, estimates of overdiagnosis derived from breast cancer incidence rates over time should take account of any longterm underlying trends in incidence taking place independent of screen ing, and of the phenomenon of lead time -that is, the estimate of overdiagnosis should not include cancers detected a few years earlier than they would have been in the absence of screening. It has been pointed out that the most recent and arguably the highest profile publication, that of Bleyer and Welch [5], fails to take full account of underlying incidence trends [8], that the publica tion by Kalager et al [23] fails to fully adjust for lead time [24] and the study of Jørgensen et al [22] has been criticized on both counts [25].…”
Section: Overdiagnosismentioning
confidence: 99%
“…However, ignor ing these phenomena results in a higher cost to validity than estimating them. Duffy and Par mar [24] show that lead time alone can generate artificial increases in incidence of the order of 30-50%, and that failure to include data up to 10 years after the age that screening ceases will cause overdiagnosis to be overestimated. This suggests that almost all published estimates of overdiagnosis, including our own, exaggerate the problem of excess incidence attributable to screening [2][3][4][5]22,23].…”
Section: Overdiagnosismentioning
confidence: 99%
“…3,4 The reason for this is that, because all cancers are latent for at least some time, the introduction of screening always produces a rapid increase in disease incidence. This increase in incidence is attributable to a combination of overdiagnosed cases and non-overdiagnosed cases whose date of detection has been brought forward in time by the screening test.…”
mentioning
confidence: 99%
“…However, a simulation study 4 showed that this method may require waiting for many years. A recent report from the Canadian National Breast Screening study 5 waited 10 years after the end of the initial 5-year screening period.…”
mentioning
confidence: 99%